PERANCANGAN ALAT BANTU MOBILITAS PASIEN PARALISIS - Rizal Indrawan; Onika Ovan Fanani; Mohamad Hakam (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Paralysis is a paralytic condition that can be caused by various factors, such as stroke, spine injury, and polio. In Indonesia, the number ofparalysis patients is quite high, with stroke disease being the main cause. The study aims to design and analyze the patient lift structurewith a lifting capacity of 150 kg using the ASTM A871-65 material. The design is done by drawing details and performing the voltageanalysis using Autodesk Fusion 360 software. The analysis results show that the arm structure, support, and leg is safe and strong with the resulting voltage being below the material voltage permitted. The size of the tool is 1490 mm × 1675 mm × 720 mm with a weight of 73.3 kg and a crane arm length of 1203.5 mm. The arm drives a hydraulic 57211-2P from the US Jack with a capacity of 1.5 tons. The front and rear wheels are selected from the TENTE brand. The total cost of manufacture of the tool is Rp2,449,425, which consistsof the cost of raw materials of Rp2,061,300 and manufacturing costs of Rp388,125. This research is expected to be a reference in the development of patient lifting aids in the future.